ANALYSIS OF MARKETPLACE CONVERSATION TRENDS ON TWITTER PLATFORM USING K-MEANS - Ulil Amri Nasron; Muhammad Habibi (Compiler, 2020)
Businesses began to shift from the marketing process that used to use conventional media to switch to using the internet and social media. This is because the cost of marketing using the internet and social media is cheaper than using conventional media. The problem that is often faced by businesspeople when marketing on social media is that they rarely see a marketplace that is becoming a trend and is being discussed by consumers on social media, so the marketing process is carried out less than the maximum. This study aims to analyze conversation trends related to the marketplace on the Twitter platform. The method used in this study is the K-Means Clustering method. Based on the results of the study found that the application of the K-Means Clustering method can produce sufficient information as a basis for consideration of businesspeople in choosing a marketplace. Marketplace trend analysis results show that Shopee, Lazada, and Tokopedia are highly discussed marketplaces on Twitter.